Lap joint dissimilar welding of aluminium and steel sheet using tig welding - Umi Kalsom, Mohamad (2013)
Dissimilar metals TIG welding of aluminium 6061 was lap joined to steel sheet and the experiments had been conducted using the filler metals of Al-4043 Si 5 % wt and Al-4047 Si 12 % wt to fabricate the lap joint of aluminium-galvanize iron in order to investigate the mechanical properties and the macrostructure and microstructure of the samples. The lap joint of aluminium-galvanize iron was analyzed by using the NDT test, microstructure of joint, tensile test and hardness test. It was found that the thickness of the IMC layer decreased and the tensile strength of the lap joint increased with the increasing of Si content in the filler metals. The decreasing of the Si content in the filler metals increases the hardness value of samples due to smaller grain size formation. The aluminium that was positioned on the upper part of the lap joint with filler type Al-4043 has the optimum mechanical properties with the tensile strength of 76.59 MPa and the average hardness value of 72 to 82 HV.